2022
DOI: 10.1111/gcb.16113
|View full text |Cite
|
Sign up to set email alerts
|

Deep demersal fish communities respond rapidly to warming in a frontal region between Arctic and Atlantic waters

Abstract: The most prominent impact of climate warming on marine ecosystems are distributional shifts in fish, which influence species interactions and food web organization. For shallow continental shelf seas, this usually implies a poleward shift or movement to deeper waters to retreat in cold water refuges (Dahlke et al., 2018;Fossheim et al., 2015;Pinsky et al., 2013). Although more than 90% of the habitable oceans' volume lies below 200 m, long-term studies of biodiversity in slope and deep-sea regions are rare (Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 92 publications
2
7
0
Order By: Relevance
“…This causes the depth profile of functional dispersion to shift from having a peak at around 900 m in 1998–2004 to an increasing trend with depth throughout the investigated depth range in 2010–2016, an outcome also influenced by species evenness increasing with depth. The transition phase in 2005–2010 is consistent with rapid changes in fish community abundances reported within this period (Emblemsvåg et al, 2022). Lower species richness and functional richness at 400 m depth in the years after 1998–2004 and the concomitant increase in these indices below 400 m depth could indicate redistribution towards deeper waters, as suggested for sub arctic species in west Greenland (Lekanda et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…This causes the depth profile of functional dispersion to shift from having a peak at around 900 m in 1998–2004 to an increasing trend with depth throughout the investigated depth range in 2010–2016, an outcome also influenced by species evenness increasing with depth. The transition phase in 2005–2010 is consistent with rapid changes in fish community abundances reported within this period (Emblemsvåg et al, 2022). Lower species richness and functional richness at 400 m depth in the years after 1998–2004 and the concomitant increase in these indices below 400 m depth could indicate redistribution towards deeper waters, as suggested for sub arctic species in west Greenland (Lekanda et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…The three depth strata and time periods were based on results from Emblemsvåg et al (2022), which showed that most temporal changes in fish community structure were observed in depths between 300 and 1000 m from 2005 until 2010, whereas little temporal change was observed in the shallower and deeper strata and before 2005 or after 2010. Data were analysed using software R version 4.0.3 (R Core Team, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations